2008
DOI: 10.1104/pp.108.126862
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Autonomously Activated Plant ADP-Glucose Pyrophosphorylase  

Abstract: ADP-glucose pyrophosphorylase (AGPase) catalyzes the rate-limiting step in starch biosynthesis in plants and changes in its catalytic and/or allosteric properties can lead to increased starch production. Recently, a maize (Zea mays)/potato (Solanum tuberosum) small subunit mosaic, MP ], containing the first 198 amino acids of the small subunit of the maize endosperm enzyme and the last 277 amino acids from the potato tuber enzyme, was expressed with the maize endosperm large subunit and was reported to have fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Since P i competitively reverses allosteric activation by ligands such as 3-PGA, the apparent inhibition constant for P i was measured in the presence of each of the three activators (Table III). In the absence of allosteric activators, very little inhibition by Pi is observed (Boehlein et al, 2009 (Fig. 4).…”
Section: Expression and Preliminary Characterization Of Mutant Enzymesmentioning
confidence: 93%
See 1 more Smart Citation
“…Since P i competitively reverses allosteric activation by ligands such as 3-PGA, the apparent inhibition constant for P i was measured in the presence of each of the three activators (Table III). In the absence of allosteric activators, very little inhibition by Pi is observed (Boehlein et al, 2009 (Fig. 4).…”
Section: Expression and Preliminary Characterization Of Mutant Enzymesmentioning
confidence: 93%
“…Except for the Sh2 R381A variant, site-directed mutagenesis involved PCR amplification of the entire plasmid as described previously (Boehlein et al, 2009). Two reverse-complementary primers containing the desired mutations were used to initiate amplification by vent DNA polymerase.…”
Section: Site-directed Mutagenesismentioning
confidence: 99%
“…CELL on May 9, 2018 by guest http://ec.asm.org/ the introduction of an AGPase that does not require 3-PGA, such as the Mos(1-198)/SH2 AGPase, which still has activity even without the presence of an activator (14). Decreasing starch degradation in microalgae.…”
mentioning
confidence: 99%
“…Phosphate exhibits a K i,app of only approximately 3.0 mM in the presence of 5.0 mM 3-PGA. We have also shown that concentrations of P i near the K i,app value inhibit activity only weakly in the absence of 3-PGA; in fact, P i actually activates the enzyme at low substrate concentrations (Boehlein et al, 2009). Fig.…”
Section: Initial Velocity Studies In the Presence Of P Imentioning
confidence: 95%
“…In the presence of 5.0 mM P i or the absence of effector, 0.2 mg of enzyme was used and the ATP concentration was varied from 0.25 to 10 mM with G-1-P concentrations varied from 2.0 to 15 mM. Initial velocities were determined spectrophotometrically by following the production of PP i during ADP-Glc synthesis, as described previously (Boehlein et al, 2008(Boehlein et al, , 2009). Assays were duplicated and averages are presented.…”
Section: Initial Velocity Studiesmentioning
confidence: 99%